THE IMPLEMENTATION OF STATE SHARIA SECURITIES BASED (SUKUK) VALUE CHAIN AT MAJENE STATE ISLAMIC COLLEGE - Fathurrahman Thaha (Universitas Islam Negeri Alauddin Makassar, 2019)
This paper is mainly concernced on how to implement state sharia securities using the value chain basis at Majene State Islamic Institute. This type of research is descriptive qualitative research, using a phenomenological approach, the data sources in this study, including primary data in the form of the results of field studies conducted at this college, and secondary data in the form of documents that are considered supportive and relevant to research studies. The results of the study showed that the activities at Majene State Islamic College consisted of: (1) main activities, including: selection of prospective new students, academic activities, teaching and learning processes, initialization and promotion, research and community service. (2) supporting activities, including: the procurement of infrastructure and financing of State Sharia Securities which are supported by HR management and financial management that is illegal. The two activities have relevance, so that a value chain is formed which produces benefits in the form of security, health, comfort and convenience of State Sharia Securities buildings from State Sharia Securities , and the value of benefits, in the form of maintaining religion, soul, mind and wealth. Because the end result of this value chain is benefit, the actual activity of procuring SBSN financing facilities at Majene State Islamic Institute, researchers have the conclusion that the concept of Islamic value chain is formed.